Why are mini-implants lost: The value of the implantation technique! - Fabio Lourenço Romano; Alberto Consolaro (Dental Press Journal of Orthodontics, 2015)
The use of mini-implants have made a major contribution to orthodontic treatment. Demand has aroused scientific curiosity about implant placement procedures and techniques. However, the reasons for instability have not yet been made totally clear. The aim of this article is to establish a relationship between implant placement technique and mini-implant success rates by means of examining the following hypotheses: 1) Sites of poor alveolar bone and little space between roots lead to inadequate implant placement; 2) Different sites require mini-implants of different sizes! Implant size should respect alveolar bone diameter; 3) Properly determining mini-implant placement site provides ease for implant placement and contributes to stability; 4) The more precise the lancing procedures, the better the implant placement technique; 5) Self-drilling does not mean higher pressures; 6) Knowing where implant placement should end decreases the risk of complications and mini-implant loss.